Digital Literacy Improvisation in Improving Teacher’s Pedagogical Competence - Rahmandani, Fahdian; Trisakti Handayani; Moh. Wahyu Kurniawan (Jurnal Pendidikan dan Pengajaran, 2025)
There are still many teachers who feel less confident and do not have adequate technology skills in managing learning. This condition has an impact on the low pedagogical ability of teachers in integrating technology optimally in the learning process. This study aims to analyze the contribution of the TPACK approach in improvising digital literacy to significantly improve teachers' pedagogical competence. The type of research used is quantitative with a concurrent triangulation design. The subjects of this study were 428 teachers participating in professional education from various regions in Indonesia. Data collection techniques were conducted through questionnaires, interviews, and documentation, with instruments in the form of questionnaire sheets. Data analysis used product moment correlation and multiple correlation tests. The results showed a significant relationship between the application of the TPACK approach and teachers' pedagogical competence. The conclusion of this study is that digital literacy through the TPACK approach can effectively improve teachers' pedagogical competence. The implication of this study shows the importance of strengthening TPACK training programs in professional education to support teachers' readiness to face the challenges of technology-based learning in the 21st century.